Arginine, scurvy and Cartier's "tree of life" - Durzan Don J (BMC, 2009)
Abstract Several conifers have been considered as candidates for "Annedda", which was the source for a miraculous cure for scurvy in Jacques Cartier's critically ill crew in 1536. Vitamin C was responsible for the cure of scurvy and was obtained as an Iroquois decoction from the bark and leaves from this "tree of life", now commonly referred to as arborvitae. Based on seasonal and diurnal amino acid analyses of candidate "trees of life", high levels of arginine, proline, and guanidino compounds were also probably present in decoctions prepared in the severe winter. The semi-essential arginine, proline and all the essential amino acids, would have provided additional nutritional benefits for the rapid recovery from scurvy by vitamin C when food supply was limited. The value of arginine, especially in the recovery of the critically ill sailors, is postulated as a source of nitric oxide, and the arginine-derived guanidino compounds as controlling factors for the activities of different nitric oxide synthases. This review provides further insights into the use of the candidate "trees of life" by indigenous peoples in eastern Canada. It raises hypotheses on the nutritional and synergistic roles of arginine, its metabolites, and other biofactors complementing the role of vitamin C especially in treating Cartier's critically ill sailors.